Overcoming Violence Against Children in School: Study on the Role of Education Stakeholders - Pramono, Wahyu (Komunitas, 2018)
Data on violence against children are only a few reported but in reality more than reported. School is one of the locations of acts of violence against children. Preventing violence against children cannot just be handed over to the police, but must involve other education stakeholders in the school. This paper looks at the role of education stakeholders in preventing violence in schools. A qualitative approach used to understand the problems be researched, data taken by the use of in-depth interviews and obeservasi. The research was done in senior high shool  "X" Bukitinggi City and  senior high school  "X"  Padang City. A description of the cases of violence that occurred at school and the way in which schools dealt with them gave an indication that education stakeholders had a sufficient role in overcoming or preventing violence. However, education stakeholders are less empowered in carrying out this role. Education stakeholders actually have the strength and authority but are less brave to use these powers and authorities to take action that can reduce or prevent acts of violence against children in school. Although their roles, duties and functions are clearly regulated in existing government regulations.